A semântica global em práticas discursivas indígenas tupiniquins - Recla, Adriana (2014)
This research is about the global semantics in tupiniquins discursive practices. We take as object of analysis 46 discourses that are in the collection Os tupiniquim e guarani contam..., organized by Edivanda Mugrabi (2005). Our aim is to examine how the dimensions of the global semantic operate in the functioning of the cultural practices of everyday life experienced by the tupiniquim subjects, and show the effects of meaning present there. This theme is pertinent because the representations of tradition and the historical and sociocultural traits, that are linguistically embodied in the corpus, help in verify interdiscursive relations, subjectivity and forms of cultural expression that permeate tupiniquim discursive practices. We are based on the assumption that each discursive function has its relevant marks and that there is a system of global constraints governing all discourses, we defend the thesis that the organization of the coercive elements of tupiniquins indigenous discursive practices stems from the global semantics, which governs all aspects and functions as a constraint network. Our theoretical foundation is the Discourse Analysis, considering the French studies, in particular, the perspectives offered by Maingueneau (1993, 2004, 2005b, 2006a, 2007, 2008a). We elected as analytical categories interdiscourse, scenes of enunciation (emphasizing the scenography), plans of global semantic (vocabulary, intertextuality, theme, status of the enunciator and co-enunciator, discourse deixis, mode of enunciation and cohesion and the discursive ethos). We noted that the indigenous discourse can be grasped in its multiple dimensions, assuming the global semantics, since linguistic materiality are present in the subject, status annunciator and co-enunciator, language code, cohesion and enunciation mode, deixis, intertextuality, ethos, scenography. Through these elements, the indigenous discursive otherness manifests, allowing effects of meaning that came from an integration of the discursive level. We observed that in the indigenous people discourse is revealed different ethos that participate in the construction of the scenography, in which resonates, for example, the voice of the indigenous people, of the white/ masterful man, of supernatural beings, of the enunciator, in order to establish the discursive effects. The ethos emerges in a speech that is indigenous, but it incorporates the constraints of religious, mystical, superstitious speeches, among others. Based on the results achieved, we considering that the global semantics, on wich the indigenous discourse also is structured, allows the deepening/ understanding of the limits of discourse, considering we recognize, based on Maingueneau (2005b), that the system installs the semantic constraints principles that make native speech belonging to a certain position